2023
DOI: 10.1177/21501351221149416
|View full text |Cite
|
Sign up to set email alerts
|

Performance of CardioCel in Cardiac Surgery: A Systematic Review

Abstract: A systematic review was performed for evaluation of the performance of CardioCel® in cardiac surgery. The review included all studies published from January 2013 to December 2020. We conclude that CardioCel is a strong, flexible tissue substitute with good handling characteristics and a low incidence of thrombosis, aneurysm formation, infection, or structural degeneration. It can be used for a variety of intracardiac and extracardiac repairs of congenital heart defects in all age groups with good durability at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(137 reference statements)
0
1
0
Order By: Relevance
“…Patukale et al 1 reported a systematic review of the published papers on the use and performance of CardioCel ® surgery. This ADAPT ® treated bovine pericardial patch is claimed to be a flexible and durable “scaffold,” which promotes tissue ingrowth claims while resisting degeneration, deformation, and calcification; therefore, reducing the need for reintervention.…”
mentioning
confidence: 99%
“…Patukale et al 1 reported a systematic review of the published papers on the use and performance of CardioCel ® surgery. This ADAPT ® treated bovine pericardial patch is claimed to be a flexible and durable “scaffold,” which promotes tissue ingrowth claims while resisting degeneration, deformation, and calcification; therefore, reducing the need for reintervention.…”
mentioning
confidence: 99%